A study of the UPHSI Democratized Admission Policy impact on students' achievement - Valencia, Irene N.; Samentar, Lorena P.; Belleza, Raphael V.; Jardeleza, Dolores H. (Danyag :the UPV journal of humanities and social sciences, 2004)
'Using the CIPP (Context, Input, Process, Product) model of Stufflebeam as framework, this study examined the performance of students who enrolled under the UPHSI democratized admission policy from school year 1989-1990 to 1996-1997. Eight batches (932) of students were selected as the subject pool for the study. From this group, a random sample of 95 students and alumni were selected to provide data on the academic and social integrations and other forces that shaped their performance in the high school. Results of students' participation in the program provided ample evidence that the characteristics of the teachers and classroom procedures had greater impact on determining the educational progress of students under the policy. Other findings pointed to the pivotal role of the family in the students' academic success. Findings on the educational outcomes of the policy indicated no significant difference in the academic performance of students under the democratized admission policy and those who were at UPHSI prior to the policy. The marked difference was their performance in the UPCAT where there was a drastic decrease in the mean percentage of qualifiers. Educational policy implications and recommendations were discussed."